PENANGANAN KEBIASAAN YANG SULIT DIKENDALIKAN PADA ANAK USIA DINI SEBAGAI SALAH SATU SYARAT DALAM PENDIDIKAN PRA-SEKOLAH - Hermahayu, Hermahayu (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2011)
With expanding numbers of children attending pre-school provision there is an increased prevalence of children whom staff perceive as presenting ,hard to manage? behavior. Handling hard-to-manage behaviours in early childhood is very important for every preschool provision. Result showed that aggression, inability to share and refusal were perceived as the most prevalent and worrying (Foot, et al, 2004). Exclusion, explanation and distraction were the most frequently used strategies for handling such behaviours. There are six behavior management strategies that good to used by teacher, consistency and flexibility of management these strategies, and parental communication and involvement.